Induction drive system with DSTATCOM based asymmetric twin converter - P Anusha; B V Rajanna (Institute of Advanced Engineering and Science, 2020)
High power demands are usually met by advanced power electronics converters in several large utility and electric drives applications. Applications from high power drives commonly uses solution based multi pulse and multilevel converters. A common DC link with atleast one voltage source converter (VSC) working with almost fundamental switching frequency are used in converters of multipulse type, and each output module is connected with the multipulse transformer in series. When compared to that of solution with single-VSC, Several VSCs generating different triggering pulses are adjused in order to achieve current injected with low specified total harmonic distortion (THD) with losses of abridged switching. Huge structure in complexity and expensive cost expenditure of the multipulse transformer is the major limitation of this scheme. DC link split capacitors in addition are eliminated by modifying the topology of the circuit. Thus, the independent voltages of the DC capacitor are controlled and decreased in number and the flow of third harmonic current component in the transformer is eliminated. The scheme of the designed controller is depending on the derived mathematical system model. Simulaion observation is used to check the scheme performance and efficiency in a detailed way with drive control technique.